2015
DOI: 10.1121/1.4908239
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of the accuracy of a vibroacoustic model for sandwich-composite panels

Abstract: This paper presents a detailed experimental validation of a general laminate model to predict the vibroacoustic behavior of flat sandwich-composite panels. The accuracy of the model is investigated using a thin and a thick sandwich panel over a large frequency band. Several indicators are compared including the structural wavenumber, modal density, damping loss factor, radiation efficiency, and sound transmission loss. The accuracy of a simpler model based on identifying effective properties of an equivalent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 12 publications
0
6
0
1
Order By: Relevance
“…In addition, it was observed that altering the mechanical properties of the plates or their structural size will shift and depress their resonance frequency; and when the modulus was also altered, a depression in the extreme values were noticed. An experimental investigation of the vibro-acoustic response of flat, thin and thick sandwich composite panels was performed by Cherif and Atalla [74]. The general laminate model and the equivalent orthotropic panel model were used to predict the STL of the structures.…”
Section: Composite Flat Panelsmentioning
confidence: 99%
“…In addition, it was observed that altering the mechanical properties of the plates or their structural size will shift and depress their resonance frequency; and when the modulus was also altered, a depression in the extreme values were noticed. An experimental investigation of the vibro-acoustic response of flat, thin and thick sandwich composite panels was performed by Cherif and Atalla [74]. The general laminate model and the equivalent orthotropic panel model were used to predict the STL of the structures.…”
Section: Composite Flat Panelsmentioning
confidence: 99%
“…Guillaumie [10] studied the modal density of honeycomb sandwich panels with composite faces based on the formula derived by Clarkson [2] and Renji [5]. Cherif and Atalla [11] investigated the modal density of sandwich composite panels http experimentally. Results indicated that combining the input mobility method at low frequency and the wavenumber method at mid and high frequency could obtain better results.…”
Section: Introductionmentioning
confidence: 99%
“…A recent article by Cherif and Atalla [24] discusses in detail the measurement vs predictions of different vibroacoustic indicators of two composite sandwich panels (wavenumbers, radiation efficiency, modal density, damping loss and transmission loss). In particular, the use of the wavenumber measurement to estimate the modal density and the radiation efficiency is discussed.…”
Section: Introductionmentioning
confidence: 99%